PERENCANAAN KOLAM PELABUHAN PONDOK DAYUNG FASARKAN TANJUNG PRIOK JAKARTA UTARA - Agus Ristiyanto; Asif Murtadlo; Salamun Salamun; Hary Budieny (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Ports of Pondok Dayung is one of the special port designation refers to as one of the supporting facilities and infrastructure facilities NKRI defense, such as privatization TNI navy military has its have means to sea port don't depend on other agencies. Planning a pool port of Pondok Dayung Fasarkan design covering breakwaters, design port dock, grooves cruise design, as well as design lap pool port. Functionally, this port will be used as a berthing dock and military vessels, as well as a repair ships for the Navy in particular regional western Indonesia and the surrounding region. Data processing in the planning include wind speed data processing used for forecasting wave generation in the area of the deep, significant wave height values obtained (Ho = 1.53 m) and significant wave period (To = 9.585 sec) using wave probabilias according Gumbel distribution (Fisher method type 1) when repeated waves during the 50-year plan. Data processing tidal water of the sea as well as the face of map data bathimetry high elevation used as reference breakwater planning and building a dock, from the calculation of the value obtained tidal water of sea level plan HHWL = + 51.4 cm, MSL = ± 0.0 cm, and LLWL = -34.6 cm. A fleet of data used as reference calculation wide planning a groove cruise obtained wide a groove 216 m (two paths) , and large the depth of the draft of the port plan the pool D=± 12.25 m from the sea bet. Data geotek worn to find out the characteristics of the ground used as reference planning breakwater type of the building , and planning foundation structure a wharf. Planning breakwater building used type of sloping side (1: 1.5) planned a total length L = 1292 m, the number of layers n = 2 Secondary layers thick layer t = 1 m heavy pieces of stone W = 168-200 kg for layers in the core layer of heavy point W = 16-20 kg, and the design elevation mercu of breakwater ± 3.79 m from MSL. Plan a wharf a total length of 252 m with elevation plan + 1,07 m of msl, plan a structure of plates thick the floor 20 cm, foundation structure piles spun pile Ø 50 cm with concrete quality K 500. Dock facilities that Fender type V (400H 1000L) with a impact energy capacity of 160 kN, as well as the type fastening a Bollard with pull capacity of 35 tons. During the planning there are several aspects of which suggested to examined more detail particularly on the big problem the value of sedimentation tranport large and shallow , with such a large value of sediment transport and sedimentation occurred in the port basin can be calculated and minimized optimally.